DESKRIPSI DAN EKSPLANASI DALAM ETNOGRAFI - Syahrizal Syahrizal (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2015)
The work of an anthropologist or ethnographer can not be separated from the process of description and explanation. This task can be regarded as the final stage of the task of an anthropologist in the research process. The research report is directly related to the description and explanation. Descriptions are the defining descriptive research findings, in conformity with the purpose of research in terms of how. While the explanation is an explanation of the phenomenon in the sense why. Descriptions and explanations can be separate, but both are inextricably linked, a researcher can give  only a descriptive overview of the research results but can not without any explanatory description. A only descriptive study of  fact can not be said scientific, because research must be able to explain why of the phenomenon. This article discusses how the description of the form of social life is running, and then explain why that phenomenon occurs. Making the transition from what to why it is a dilemma, but for ethnographers available resources to make it easier to detect and appreciate supported by the description. Explanation can be identified as a causal explanation and theoretical explanation. Phenomena become clear causal explanation based on the relationship associations of the facts found in the field. While the theoretical explanation is based upon the theory of explanation also means perspective. As Geertz their explanations by theoretical espoused ie interpretive explanation.